INVESTIGATION ON THE AVAILABILITY OF AMINO ACIDS FROM DIFFERENT ANIMAL PROTEIN SOURCES IN GOLDEN COCKERELS - Saima; M. Akhter; M. Z. U. Khan; M.I. Anjum; S. Ahmed; M. Rizwan; M. Ijaz (Journal of Animal and Plant Sciences, 2008)
The direct relationship exists between the quality of an animal protein source and its available amino acids. A number of samples of each of the fish meal, feather meal, meat meal and blood meal were analyzed for their proximate composition. Then two samples of each ingredient one having the highest (grade A) other with lowest crude protein (grade B) were selected. They were analyzed for their available amino acids. The average availability of fifteen amino acids in high grade fish meal, feather meal, meat meal and blood meal were 85.68, 80.36, 85.53 and 77.62 percent, respectively. Whereas average availability of fifteen amino acids in low grade fish meal, feather meal, meat meal and blood meal were 78.12, 76.60, 67.10 and 69.46 percent, respectively. All protein sources were force fed to the birds and excreta samples were collected during the trial. Feed and excreta samples were analyzed for amino acid. The available amino acid contents of a feed protein were assayed by measuring the live weight gain, feed conversion efficiency, nitrogen retention of the chicks given the intact protein as a supplement to a diet deficient in a particular amino acid under investigation. It was clear after the determination of availability of each amino acid that more amino acids are available in high grade animal protein sources as compared to low grade animal protein source. Thus it was concluded that quality of feed ingredients impose direct effect on their available amino acids profile.
Keywords: Animal protein; quality; available amino acids; cockerels